Vernacular gardens ́ floristic composition in three Mexican rural communities - Leyva Trinidad, Doris Arianna; Pérez Vázquez Arturo; Vargas-Mendoza Mónica de la Cruz; Gallardo López Felipe; García Albarado J. Cruz; Pimentel Aguilar, Silvia (Revista Mexicana de Ciencias Agrícolas, 2018)
Mexico is one of the five megadiverse countries in the world, being the f lora the most important component in social, economic and biological terms. This biodiversity is partly reflected in the flora of the rural ornamental gardens. For this reason, the objective was to describe the floristic diversity within the gardens of three Mexican rural communities. However, it is unknown on what proportion the native ornamental flora is actually present. The research was conducted in 2012 in three Mexican rural communities (San Felipe Cuapexco in Puebla; Tepexilotla and Angostillo in Veracruz). The existing flora within the gardens was collected and taxonomically identified, calculating Simpson’s and Shannon-Wiener ́s diversity indexes. Of the three communities, San Felipe Cuapexco had the highest species diversity (121). The largest number of species were exotic (107 species, 58%) compared to native(79species,42%).Weidentifiedthreetypesofstrata: herbaceous (62.3%), shrub (23.1%) and arboreal (14.5%). Despite the geographical location of each community, the floristic composition of these gardens was quite similar, identifying a total of 186 species belonging to 70 families and 156 genera. Roses are the most abundant species within the gardens, due to its characteristics such as color and flower type. We concluded that, in the f loristic composition of these gardens, exotic species had a higher proportion compared to native American ́s, let alone the native Mexican ́s. The most abundant species in the vertical structure were herbaceous, with ornamental and medicinal uses. The existing species variability within the gardens is determined by the diversity of uses, largely for ornamental, edible, spicing, medicinal and functional.